The Sustainable Development Goals Diffusion and Contestation in Asia and Europe (Taylor & Francis, 2023)
There have been significant efforts to implement the Sustainable Development Goals (SDGs) at multiple levels of governance across all regions of the world. However, the manner in which the global governance norms underlying the SDGs are actually being diffused is under-researched and not well understood. This book considers the promotion of the SDGs through the lens of norm diffusion theory, with a focus on three SDG policy areas; health, education and decent work. A distinctive feature of the book is that it offers multiple original case studies of SDG norm diffusion involving Asian and European actors. A unique feature is that the case studies in the book identify relevant SDG norm senders and norm receivers, and examine the relationship between them. The book also challenges the assumption that the SDGs themselves are static and unchanging, and reveals how SDG norms are dynamic and can be reformulated as a result of contestation between norm senders and norm receivers. As well as introducing a diverse and original set of case studies, the book therefore allows readers to deepen their understandings of the policy diffusion mechanisms by which SDGs are diffused, and grasp the patterns of success and failure in the implementation of these policies.
English
Keywords: Business & management; Central government policies; Educational strategies & policy; Regional & area planning; education for sustainability, global governance, norms, SDGs, wellbeing discourse